The Delta Queen Cookbook : The History and Recipes of the Legendary Steamboat - Nobles, Cynthia LeJeune, 1954- (Book collections on Project MUSE., 2012)
The world's last authentic overnight wooden steamboat, the Delta Queen cruised America's inland waters from 1927 through 2008, offering passengers breathtaking views, luxury accommodations, rousing entertainment, and southern-style feasts. For over eighty-two years, chefs in the small galley served memorable meals-from fried chicken and crawfish en croûte to strawberry shortcake and beignets. The Delta Queen Cookbook brings the Delta Queen's story to life with an engaging historical narrative and over 125 recipes prepared by the steamboat's former chefs during their tenures in the cookhouse. N.